Inferior Vestibular Neuritis: Diagnostic Criteria, Clinical Features, and Prognosis—A Focused Review - Gabriela Cornelia Musat; Mihai Alexandru Preda; Ionut Tanase; Adina Zamfir Chiru Anton; George G. Mitroi; Ovidiu Musat; Alina Lavinia Antoaneta Oancea; Mihaela Roxana Mitroi (Medicina)
Purpose: This review aims to analyze the diagnostic methods used to evaluate inferior vestibular nerve neuritis. Methods: We performed an electronic search on the PubMed database for clinical studies investigating the diagnostic techniques used for inferior vestibular nerve neuritis. Results: We initially identified 114 records in our search. After applying the inclusion and exclusion criteria, we narrowed it down to 12 studies. These studies collectively examined a total of 642 patients diagnosed with vestibular nerve neuritis, 64 of whom had inferior vestibular neuritis. Conclusions: The inferior vestibular neuritis is an unfrequent form of vestibular neuritis, often misdiagnosed. The diagnosis of inferior vestibular neuritis (IVN) is based on clinical history and vestibular testing, specifically reduced posterior canal gain on video head impulse test (vHIT), absent cervical VEMP (cVEMP), normal caloric responses, and preserved ocular VEMP (oVEMP). This review highlights the gaps in current diagnostic strategies and emphasizes the need for integrating advanced vestibular testing methods to enhance diagnostic accuracy for inferior vestibular nerve neuritis. Future studies should address the standardization of diagnostic protocols to facilitate broader clinical application.